2018
DOI: 10.3389/fpsyg.2018.02188
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Testosterone Increases Decoy Effect in Healthy Males

Abstract: There is increasing interest in the role played by testosterone in economic decision-making and social cognition. However, despite the growing body of findings in this field of research, no empirical study to date has tested whether testosterone modulates decision-making when an asymmetrically dominated decoy option is introduced in a choice set. Within a choice set that comprises two options, an asymmetrically dominated decoy option is a third option that, when introduced in the choice set, is much worse than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…We found that mainly individuals aged 26-30, females, of Black or Black British or Arab ethnicity, or those with a Bachelor's degree completed the survey with the target incentive. While studies suggest that the decoy effect emerges at a young age and that testosterone is associated with inconsistent decisions [39,40], our study does not indicate that male participants were more likely to react to the decoy. Our study presents limitations that warrant further investigation.…”
Section: Plos Onecontrasting
confidence: 95%
“…We found that mainly individuals aged 26-30, females, of Black or Black British or Arab ethnicity, or those with a Bachelor's degree completed the survey with the target incentive. While studies suggest that the decoy effect emerges at a young age and that testosterone is associated with inconsistent decisions [39,40], our study does not indicate that male participants were more likely to react to the decoy. Our study presents limitations that warrant further investigation.…”
Section: Plos Onecontrasting
confidence: 95%
“…Over the past decade, several studies have shed light on the relationships between circulating testosterone and consumer choice (Stanton, 2017). For example, testosterone administration has been shown to increase the decoy effect (Liao et al, 2018). Additionally, testosterone is associated with status-related consumption.…”
Section: Circulating Testosteronementioning
confidence: 99%